Do teenagers recover from traumatic situations? Identification of types of change and relationship with psychopathology and coping. (September 2020) - Planellas, Irina; Magallón-Neri, Ernesto; Kirchner, Teresa; Forns, Maria; Calderón, Caterina
Highlights: Traumatic events in adolescence have a harmful effect on mental health. Non-interpersonal traumas occurring more frequently than interpersonal events. Adolescents generally show a good ability to recover from trauma. Abstract: Teenagers may experience potentially traumatic interpersonal and non-interpersonal events in everyday life that could cause discomfort. The general aim of this study was to explore changes over time in the perception of such discomfort and the psychopathological symptoms and coping linked to such change. The specific objectives were to: (a) describe the potentially traumatic life events (PTLEs) reported by participants; (b) analyze types of change in the distress experienced at the time that the event occurred and now according to gender and the time elapsed since the PTLE, and (c) assess psychopathological symptoms and coping styles according to four categories of change in distress (no-distress, permanence in initial distress, increased distress and decreased distress). Methods: A retrospective cross-sectional design was employed. Five hundred and fifty-three Spanish teenagers (13 to 19 years old; 60.6% female) completed the LITE-S, YSR and A-COPE-SP self-reports, which assess traumatic events, psychopathological symptoms and coping style, respectively. Results: Among the participants, 98.5% reported at least one PTLE, with non-interpersonal events more common than interpersonal events. Depending on the specific PTLE, 48% to 74% of teens reported reduced distress since the incident, a maximum of 16% reported increased distress, and between 6% and 56.5% reported permanence in the initial distress. Depending on the PTLE, anxiety and oppositional behaviors were higher in those showing increased distress, while affective and post-traumatic stress were lower in individuals showing decreased distress. Coping styles did not vary much between the types of change in distress, with the exception of searching for friendship, which was less common in adolescents who showed no distress over time. Being taken away from family caused the most persistent distress Conclusions: This study provides a useful framework for understanding the experiences of adolescents exposed to PTLEs, indicating that adolescents generally show good ability to recover from trauma. However, teens with increased and permanent distress over time have been identified as an at-risk population, and are therefore likely to be cared for by psychological or psychosocial services.